Dynamic properties of stone mastic asphalt mixtures containing waste plastic bottles - Baghaee Moghaddam, T.; Karim, Mohamed Rehan; Syammaun, T. (Elsevier, 2012)
Fatigue failure is a common problem of asphaltic concrete which can lead to pavement damage. Many studies have been conducted to find ways for increasing fatigue life of asphalt concrete mixtures. This study investigates effects of adding waste polyethylene terephthalate (PET) on stiffness and fatigue properties of SMA mixtures at optimum asphalt contents. Different percentages of waste PET with maximum size of 2.36 mm were added to SMA mixtures. Indirect tensile stiffness modulus test and indirect tensile fatigue test were conducted at temperature of 20Â°C and at three different stress levels (250, 350, 450 kPa). The results showed that stiffness modulus of mixture increased at lower amount of PET content; however, adding higher amount of PET made mixture less stiff. In addition, PET reinforced mixtures exhibit significantly higher fatigue lives compared to the mixtures without PET. Â© 2012 Elsevier Ltd. All rights reserved.